A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMK N 1 BENAI IN COMPREHENDING NARRATIVE TEXTS - Claudia, Wanda; Ras, Fakhri; Masyhur, Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study seeks to the ability of the second year students of SMK N 1 Benai comprehending narrative text. It is a descriptive research carried at from March-April 2018. There are five classes in this research. The population were 194 students, their characters are homogeneous in terms of academic achievementand age factors. The cluster random strategies technique was choosen due to that every class has equal ooportunity to be a sample group. The sample conpused of two categories, try out class (XI AK 2) and sample class (XI TKJ 2). Try out class consisted of 42 students and 40 students from sample class. In this research, the try out test aimed at acknowledging the validity of the test.. The time allocation to administer the try out test and the revised test was 60 minutes for each of them. The data were analyzed by calculating the students’ scores, classified into five level mastery, such as very poor, poor, mediocre, good and excellent. Based on the analyzing data of this research, the students’ ability in comprehending narrative text at second year students of SMK N 1 Benai was in mediocre level. Meanwhile, the mean score of the whole students’ scores was 5.81. The implication of the finding is that the second year students of SMK N 1 Benai is able enough at comprehend narrative texts.Key Word : Students’ Ability, Comprehending Narrative Texts